2013
DOI: 10.7717/peerj.88
|View full text |Cite
|
Sign up to set email alerts
|

Activity in ventral premotor cortex is modulated by vision of own hand in action

Abstract: Parietal and premotor cortices of the macaque monkey contain distinct populations of neurons which, in addition to their motor discharge, are also activated by visual stimulation. Among these visuomotor neurons, a population of grasping neurons located in the anterior intraparietal area (AIP) shows discharge modulation when the own hand is visible during object grasping. Given the dense connections between AIP and inferior frontal regions, we aimed at investigating whether two hand-related frontal areas, ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 60 publications
4
18
0
Order By: Relevance
“…This may be an important process for identification of self-body action. The system also leads to generalization of matching between actions and viewing actions executed by other individuals (Fadiga et al, 2013;Raos et al, 2006). The idea is congruent with our results that mirror neurons are found in AIP where hand-type neurons are found.…”
Section: Functional Roles Of Hand Manipulation-related Neurons In Ressupporting
confidence: 91%
See 1 more Smart Citation
“…This may be an important process for identification of self-body action. The system also leads to generalization of matching between actions and viewing actions executed by other individuals (Fadiga et al, 2013;Raos et al, 2006). The idea is congruent with our results that mirror neurons are found in AIP where hand-type neurons are found.…”
Section: Functional Roles Of Hand Manipulation-related Neurons In Ressupporting
confidence: 91%
“…We hypothesize that these neurons are capable of monitoring ongoing hand movement by comparing the corollary discharge (predicted sensory feedback) with the actual visual feedback. Notably, the activity of premotor neurons is modulated by transient visual feedback during grasping actions (Fadiga et al, 2013), demonstrating that a subset of premotor neurons is sensitive to the observation of oneʼs own grasping. Fadiga et al suggested that this modulation is due to an effect along the parietal-frontal pathway.…”
Section: Hand-type Neuronsmentioning
confidence: 99%
“…Hand movements during the task were recorded by a 3D-motion optical analyzer (Qualisys Motion Capture System; Qualisys, Charlotte, USA) and were synchronized by using the TTL signal of pad release. Setup and procedure were similar to those described by a previous work (Fadiga et al, 2013). Three small adhesive infraredreflective spheres (diameter 3.0 mm, weight 40 mg) were placed over three anatomical landmarks: the wrist (head of the ulna) and the last interphalangeal joint of thumb and index finger.…”
Section: Kinematics Recordingmentioning
confidence: 99%
“…The motion analysis software reconstructed the 3D coordinates of the markers in space and time, enabling off-line reconstruction of the movement of each marker. Movements were recorded at a sampling rate of 200 Hz, a value considered more than appropriate for the biological motion of primates (Saleh et al, 2012;Fadiga et al, 2013). Using TTL signals from the pad (at the release) and from the handle (at touch), we analyzed wrist velocity and grip aperture, i.e., the distance between the two markers placed on the fingers.…”
Section: Kinematics Recordingmentioning
confidence: 99%
“…Due to the restricted environment of functional Magnetic Resonance Imaging (fMRI), most studies investigating kinematics have used simple hand movements (e.g. [3,4]) or the mere observation of movements (e.g. [5,6]) to study the neural correlates of motor control.…”
Section: Introductionmentioning
confidence: 99%